Utilization of medicines by the Brazilian population, 2003 Características da utilização de medicamentos na população brasileira, 2003 - Marcelo Felga de Carvalho; Ana Roberta Pati Pascom; Paulo Roberto Borges de Souza-Júnior; Giseli Nogueira Damacena; Célia Landmann Szwarcwald (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
The aim of the present study was to characterize the utilization of medicines by the Brazilian population, using data from the Brazilian World Health Survey. Medicines were grouped according to the active pharmaceutical ingredient based on an adaptation of the World Health Organization standard list of essential medicines. The analysis included the characteristics of individuals who keep medicines at home and who had used them within the reference period (within two weeks prior to the interview), according to presence of medical prescription. Nearly half of the participants (49.0%) reported use of medicines during the reference period. Older and wealthier individuals and those with chronic diseases or disabilities and with poor self-rated health keep and use medicines more frequently. For 25.0% of the individuals that had used medicines during the reference period, none of the drugs had been prescribed by a health professional. Among the individuals who had medicines prescribed in the last appointment, 13.0% were unable to obtain the prescribed medication (of these, 55.0% could not afford it). The most widely utilized group was that of the analgesics (22.0%), and only 51.0% of the individuals using this type of medicine had received a medical prescription for it. O presente estudo tem como objetivo caracterizar a utilização de medicamentos na população brasileira, por meio dos dados da Pesquisa Mundial de Saúde. Os medicamentos foram agrupados de acordo com o princípio ativo baseando-se em uma adaptação da lista padrão da Organização Mundial da Saúde. A análise contemplou as características das pessoas que guardam medicamentos em casa e que utilizaram medicamentos nas duas semanas anteriores à data da pesquisa segundo a presença de prescrição médica. Quase a metade dos participantes relatou uso no período de referência (49,0%). Os indivíduos mais idosos, com maior riqueza, com doença de longa duração ou incapacidade e com auto-avaliação ruim da saúde guardam e utilizam medicamentos com maior freqüência. Entre os indivíduos que utilizaram medicamentos no período de referência, para 25,0%, nenhum foi prescrito por médico. Dentre os indivíduos que tiveram prescrição de medicamentos no último atendimento, 13,0% não conseguiram adquirir todos os medicamentos, sendo que 55,0% alegaram que não puderam pagar. A maior proporção de utilização foi encontrada para o grupo dos analgésicos (22,0%), sendo que somente 51,0% dos indivíduos que utilizaram esses medicamentos o fizeram com prescrição médica.